Parametric modeling the human calves for evaluation and design of medical compression stockings. (October 2020) - Xi, Wang; Bao, Yang; Qiao, Li; Xia, Guo; Xiaoming, Tao
Highlights: A 3D parametric model of human calves was proposed and verified. The parametric model was found effective to reduce the data complexity of all calves in database to only the 1st order principal component. With the model, methodological framework of fast reconstructing representative human calves for individual patients was proposed. A smart morphing leg mannequins were manufactured based on the model to evaluate pressure distributions or design customized compression stockings for individual patients. Abstract: Background and objective: Accurate dose of compression imposed by functional compression garments, such as medical compression stockings, is critical for medical treatment or rehabilitation. To evaluate or provide fitted compression stockings for individuals, the real curved calf shapes other than just anthropometric parameters are required. Methods: This paper proposes and verifies a simple 3D parametric model of human calf that can fast and efficiently construct representative calves for evaluation or size-design purposes. Instead of selecting feature points, shape parameters were used to characterize the real calves. Results: Based on principal component analysis and a database of 220 scanned Chinese subjects, the proposed parametric model was found as capable of largely reducing the data complexity to only the 1st order principal component with a major variance percentage of as high as 96%. A methodological framework of parametric modeling was then proposed. Results show that the proposed parametric model and method can fast produce valid representative shapes of patients' calves, with which commercial stockings can be evaluated and customized stockings can be designed. Conclusions: It can be concluded that the proposed parametric model and method can highly boost evaluation/size customization of MCSs, and will also inspire the research on customization of other compression garments.